КРИМІНАЛІСТИЧНА ХАРАКТЕРИСТИКА НЕЗАКОННОГО ПЕРЕТИНУ ДЕРЖАВНОГО КОРДОНУ ОСОБОЮ, ЯКІЙ ЗАБОРОНЕНО В’ЇЗД НА ТЕРИТОРІЮ УКРАЇНИ - Дашкевич, Валентина Андріївна, Джафаров Мурад Єльман Огли (SUPREMANCE OF LAW, 2019)
The current issues, the role and significance of the criminological characteristic in the formation of the procedure for investigating the illegal crossing of the state border by a person who is prohibited from entering the territory of Ukraine. The relationship between the elements of the criminological characteristic and the separate components of the methodology of investigation of crimes in the specifi ed sphere is considered.